Effects of tirofiban on acute systemic inflammatory response in elective percutaneous coronary interventions - Akbulut, M; Ozbay, Y; Gundogdu, O; Dagli, N; Durukan, P; Ilkay, E; Arslan, N (Taylor & Francis Ltd, 2004)
Objective: In this study the effect of a specific glycoprotein)IIb/IIIa inhibitor, tirofiban [which also has antiplatelet activity on acute systemic inflammatory responses (III) during elective percutaneous coronary intervention (PCI)] was evaluated. Patients and methods: Patients with stable angina pectoris and similar baseline characteristics who angiographically had a single lesion in their coronary arteries with a PCI performed on that lesion were enrolled in the study. One group of patients (control group, n = 52) received 0.9% NaCl (15 mL/h for 24 h) and the other group (tirofiban group, n = 55) had tirofiban (10 mug/kg bolus infusion in 3 min and 0.15 mug/kg/min for 24 h) in addition to stenting without pre-dilatation. The effect of interventional procedure on levels of cardiac troponin T (cTnT) and several parameters of acute IR (leukocytes, fibrinogen, C-reactive protein, interleukin-1, interleukin-6, interleukin-8 and tumor necrotizing factor-alpha) was assessed on blood samples obtained from all patients before PCI and at pre-specified time points after PCI. Results: During the follow-up after PCI, the number of patients becoming cTnT-positive (> 0.1 ng/mL) was greater in the control group [12 (23%) patients vs. 3 (5%) patients, p = 0.01]. However, both groups had changes (generally observed as elevations) in their levels of all inflammatory parameters during the study and C-reactive protein, interleukin-6 and tumor necrotizing factor-alpha levels were elevated significantly. Yet, no significant difference occurred between groups due to these changes in any phase of the study (p > 0.05). Conclusions: Based on the findings of this study, it was concluded that although tirofiban limits development of myocardial necrosis during elective PCI, it does not directly affect the acute systemic inflammatory responses.
Keywords: acute systemic inflammatory response; percutaneous coronary intervention; tirofiban